Novos registros de aves para a Fazenda Barreiro Rico, Anhembi-São Paulo - Antunes, Alexsander Z. [UNESP]; Willis, Edwin O. [UNESP] (My University, 2003)
We recorded eleven bird species new for the Barreiro Rico farm in Anhembi, in the state of São Paulo, southeastern Brazil. This is one of the best-known birding sites in Brazil. Three hundred and fifty nine species have been recorded after 45 years of ornithological surveys.
New bird records for the Barreiro Rico farm, Anhembi-São Paulo
Keywords: Aves; Barreiro Rico farm; New bird records; São Paulo; Southeastern Brazil